The Use of Progressive Law Phrase in Constitutional Court Decisions: Context, Meaning, and Implication: Penggunaan Frasa Hukum Progresif dalam Putusan Mahkamah Konstitusi: Konteks, Makna, dan Implikasi - Aulia, Muhammad Zulfa; Hantoro, Bimo Fajar; Sanjaya, Wawan; Ali, Mahrus (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
As an influential legal idea, Satjipto Rahardjo’s progressive law has colored various legal discourses and practices in Indonesia. Court decisions, as legal texts that record and summarize the trial process, also show that litigants, experts, and court judges often use this legal idea. This research will examine how progressive legal phrases are used in court decisions and whether the users have considered their underlying assumptions, pillars, or principles. This research is limited to Constitutional Court decisions in law review cases. The use of progressive legal phrases is generally accompanied by several progressive legal assumptions proposed by Satjipto Rahardjo. However, these are selected and used partially according to the needs and interests of their users, and thus can have bias implications when compared and examined comprehensively based on other assumptions or pillars.